L'écriture du détournement chez Jacques Ferron - Grzybowska, Aleksandra Maria (Romanica Silesiana)
The article examines the instance of triple intertextuality in Jacques Ferron's Le “Saint-Elias”. It focuses on representations of women and studies Ferron’s references to the Faust myth, to the biblical story of Mary Magdalene, to Pierre Ambroise Choderlos de Laclos’ “Les Liaisons dangereuses”, as well as to Jean Rotrou's “Saint Genest”. Keywords : Jacques Ferron; intertextuality; irony in literature; Faust myth; Mary Magdalene biblical episod; Laclos' Les Liaisons dangereuses'; Jean Rotrou's Saint Genest